Artillery Guns of the 16th–18th Centuries in Lithuanian Museums and a Private Collection - Vasiliauskas, Liudvikas (Archaeologia Lituana, 2017)
This article discusses all the original 16th–18th c. artillery guns kept and displayed in Lithuanian museums and a private collection. The guns have been grouped in accordance with their types, dates of manufacture and their storage/display locations. There are also data provided by the X-ray fluorescence (XRF) analyses of gun barrel alloys’ chemical elements. The text is supplemented by a catalogue of the abovementioned artillery guns. Keywords: artillery, kartouwe, culverin, bombard, howitzer, mortar, swivel cannon, field cannons